A qualitative study exploring patient experiences of art therapy in a female medium secure unit - Rajesh, Sharon (The journal of forensic psychiatry & psychology, 2023)
This qualitative study is the first evaluation of patient experiences of art therapy within female secure mental health services. Data was collected using semi-structured interviews and analysed using thematic analysis in 10 patients with severe and enduring mental health conditions in a female medium secure unit in South London. Four themes (expression, connectedness, coping and sense of empowerment) and nine subthemes (the art therapist, the artwork, sense of belonging, building relationships, escapism, managing emotions, control, reflection, and achievement) were identified. These themes demonstrated the participants’ positive personal experiences of art therapy. Our results add to the body of evidence supporting the positive benefits of art therapy within inpatient mental health units. Escapism and achievement were highlighted as important themes that are often less valued in the professional literature. This provides new insight, and contribution that should be considered by clinicians to help to shape the future delivery of art therapy interventions within inpatient mental health settings. We hope this encourages others to study this topic further. Future research may wish to focus on whether there are measurable improvements in wellbeing from art therapy within forensic inpatient care.